Enzymatic Modification of Apple Pomace and Its Application in Conjunction with Probiotics for Jelly Candy Production - Jolita Jagelavičiutė; Dalia Čižeikienė; Loreta Bašinskienė (Applied Sciences)
This study aimed to evaluate the applicational possibilities of enzymatically modified apple pomace (AP) in conjunction with probiotics as value-added ingredients for the production of jelly candies. AP was enzymatically modified with Pectinex® Ultra Tropical, Viscozyme® L, and Celluclast® 1.5 L (Novozyme A/S, Bagsværd, Denmark), and the soluble and insoluble dietary fibre content was determined using the Megazyme kit (Megazyme International Ireland Ltd., Wicklow, Ireland), reducing sugar content using the 3,5-dinitrosalicylic acid assay. The technological properties of the modified AP, such as its swelling capacity, water-retention capacity, oil-retention capacity, bulk density, and static and thermal emulsion stability, were evaluated. Enzymatically modified AP hydrolysed with Celluclast® 1.5 L was used for the production of jelly candies supplemented with Bifidobacterium animalis DSM 20105. The survival of probiotics in the jelly candies during in vitro digestion, the viability of probiotics during candy storage, and candy quality characteristics were analysed. Enzymatically modified AP had different carbohydrate compositions and technological properties, depending on the enzyme preparation used. Although the viability of probiotics in the jelly candies decreased during storage, a significantly higher viability of B. animalis was determined in jelly candies supplemented with hydrolysed AP compared with control candies made without AP after digestion in the saline, gastric, and intestine phases. This study shows that Celluclast® 1.5 L can be used for increasing the soluble dietary fibre in AP (18.4%), which can be further applied, in conjunction with B. animalis, for added-value jelly candy production.